Enhancement Of Students' Religious Character Through Qur'an Literacy Program At SMP IT Alhusniyah - Komariah, Nur; Safitri, Risna Safitri; Oktapia, Mila; Syakur, Syakur; Suriyah, Suriyah; Hartati , Herni (CV. Pustaka An Nur, 2025)
Community service conducted at Alhusniyah Integrated Islamic Junior High School found that Quran literacy is very important to improve students' understanding of Islamic values. This community service aims to provide experience to students of Field Experience Practice of Islamic Education Management study program. This community service uses the Participatory Action Learning System (PALS) method to improve students' knowledge of the Quran, such as letters, tajwid, and other aspects. This community service identifies four stages, namely First, identifying students who do not understand the Quran, ensuring they understand the text. Second is implementing the program, ensuring students understand the Quran and can apply it according to the knowledge that has been determined. Third, evaluating the program using formative and summative methods. Fourth is developing a program based on the evaluation results. From the results of the community service, it can be concluded that the use of the PALS methodology in the Quran literacy program has a positive impact on students' religious character, this allows them to understand the Quran with correct tajwid and good waqf, as well as discipline and responsibility for their obligations.